Ore breakage characterisation of UG2 deposits using the JK RBT - Chikochi, Christopher (Department of Chemical Engineering, 2018)
Ore breakage characterisation is a methodology that is used to determine the ore hardness, or resistance to breakage which can be compared across a database of different rock types. It thus develops a relationship between specific energy input and degree of breakage which can be applied to impact breakage in comminution devices. The present study is focussed on investigating the breakage properties of UG2 chromitite, pyroxenite, spotted anorthosite and mottled anorthosite grab samples from run-of-mine (RoM) ore stockpile (particle selection method) and cut drill core particles (cut core method). A mineralogical analysis of UG2 chromitite, pyroxenite, spotted anorthosite and mottled anorthosite was performed using Leica EZ4D optical microscope and QEMSCAN 650F to determine their mineral composition and texture. The presence of cracks in chromitite stockpile and cut drill core samples was also explored using a Nikon XTH 225 ST micro-focus X-ray system. RoM ore stockpile and cut drill core particles of each of these rock types were subjected to impact breakage in the JK Rotary Breakage Tester (RBT). The progeny particle size distributions and degrees of breakage of UG2 rock types obtained via the particle selection and cut core methods were compared. Standard breakage characterization models were fitted to the breakage data of different rock types and the relative hardness parameters compared. It was found that UG2 chromitite comprised mainly fine, isolated, round chromite grains in a plagioclase matrix. Pyroxenite samples were found to be made up of granular orthopyroxene, interstitial plagioclase and clinopyroxene. The mineralogical analysis also revealed that spotted anorthosite primarily contains plagioclase with orthopyroxene crystals forming isolated "spots" creating a poikilitic texture. Mottled anorthosite is made up of mainly plagioclase. Results from breakage tests showed that the progeny particle size distributions and the degrees of breakage for particles sourced from the RoM ore stockpile breaks into a finer product compared to cut drill core samples. This was attributed to the presence of cracks in the RoM ore particles as revealed by the tomographic scans. No visible cracks were found in the cut core particle. The ore hardness parameters were determined from fitting the breakage data to standard impact breakage characterisation models (t10 breakage and size dependent breakage model). Samples obtained via the particle selection method were consistently found to offer less resistance to impact breakage as shown by the higher Axb values compared to the cut drill core samples. Using the ore hardness classes presented by Napier-Munn et al (1999), UG2 chromitite, spotted anorthosite, mottled anorthosite and pyroxenite were thus classified as very soft, soft to very soft, soft to very soft and medium to soft respectively. The hardness indicator, 3600.M.fmat.x, for each size class determined using the parameters obtained from the size dependent breakage model decrease with an increase in the parent particle size. This shows that particles become more resistant to impact breakage as the initial particle size increases. However, for pyroxenite, spotted and mottled anorthosite, the indicator decreases between the particle sizes 14 to 28.6 mm but then increases for 41.1 mm.